1996
DOI: 10.1093/jee/89.6.1521
|View full text |Cite
|
Sign up to set email alerts
|

Permethrin-Impregnated Yarn: Longevity of Efficacy and Potential Use on Cylindrical Fiberglass Stable Fly (Diptera: Muscidae) Traps

Abstract: Efficacy of permethrin-impregnated orion yam against stable Hies, Stomoxys calcitrans (L.), was 6-8 wk under simulated field conditions. Numbers of stable Hiescaptured on corrugated cylindrical fiberglass traps painted with an adhesive indicated that these traps are attractive enough to be used in the field with treated yam applied. Heasonsfor variability of yam impregnation and the use of yam on cylinder traps are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…In particular, Meifert et al (1978) used permethrin-treated alsynite targets at a rate of one per Þve head of cattle at two sites in Florida, and estimated that the units removed Ͼ30% of the stable ßy popu-lation during their study. Our results when joined with those of Foil and Younger (2006) seem to be more promising than those of previous studies, where pyrethroids (permethrin) were combined with alsynite Þberglass panels or cylinders (Meifert et al 1978, Hogsette andRuff 1996). Foil and Younger (2006) conducted electric grid studies and found that half blue and half black 1-m 2 UK trigger targets attracted a 6.1-fold higher number of stable ßies than alsynite cylinder traps.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…In particular, Meifert et al (1978) used permethrin-treated alsynite targets at a rate of one per Þve head of cattle at two sites in Florida, and estimated that the units removed Ͼ30% of the stable ßy popu-lation during their study. Our results when joined with those of Foil and Younger (2006) seem to be more promising than those of previous studies, where pyrethroids (permethrin) were combined with alsynite Þberglass panels or cylinders (Meifert et al 1978, Hogsette andRuff 1996). Foil and Younger (2006) conducted electric grid studies and found that half blue and half black 1-m 2 UK trigger targets attracted a 6.1-fold higher number of stable ßies than alsynite cylinder traps.…”
Section: Discussionsupporting
confidence: 64%
“…Traps or treated targets for the control of stable ßy populations have shown promise in several studies (Hogsette et al 1987;Rugg, 1982;Hogsette and Ruff 1996). In particular, Meifert et al (1978) used permethrin-treated alsynite targets at a rate of one per Þve head of cattle at two sites in Florida, and estimated that the units removed Ͼ30% of the stable ßy popu-lation during their study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, placing an Olson sticky sleeve over the fabric used for the BCTs somehow reduced the qualities that make the BCTs attractive when not covered. In one study, AFTs with an adhesive applied directly to the surface of the fiberglass captured almost twice as many stable flies as AFTs covered with sticky sleeves [Hogsette and Ruff, ]. Thus, sticky sleeves reduced the attraction of Alsynite cylinder traps and must do the same in some manner for the BCTs.…”
Section: Discussionmentioning
confidence: 99%
“…By merging the developments in insecticides with new modes of action with traditional concepts of delivery using our knowledge of fly behavior, we expect to modify and develop, in conjunction with industry, new technologies of fly control that will successfully solve fly problems for deployed military. For instance, flies prefer to rest on strings and cords and can be controlled using insecticide treated yarn (Hogsette and Ruff 1996). They also are attracted to surfaces that reflect ultraviolet light (Patterson et al 1980, Patterson and Koehler 1982.…”
Section: Introductionmentioning
confidence: 99%